How to manage people through continuous change - Goman, Carol Kinsey (Stanford executive briefings, 2007)
Change is no longer an event. Change is business as usual. Success today is dependent on keeping your work fornce engaged while your organization is constantly being turned upside down. Carol Kinsey Goman explains what it takes to go from "surviving change" to "thriving on change".